Athos-Graphene: Computational discovery of an art-inspired 2D carbon anode for lithium-ion batteries - Lima, Kleuton A.L.; Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Sambrano, Julio R. [UNESP]; Dias, Alexandre C.; Galvão, Douglas S.; Ribeiro, Luiz A. (Elsevier, 2025)
Two-dimensional (2D) carbon allotropes have attracted growing interest for their structural versatility and potential in energy storage and nanoelectronics. We propose Athos-Graphene (AG), a novel 2D carbon allotrope inspired by the geometric patterns of Brazilian artist Athos Bulcão. Designed using density functional theory, AG features a periodic structure with high thermodynamic and thermal stability, as evidenced by a low cohesive energy (-7.96eV/atom), the absence of imaginary phonon modes, and robust performance in ab initio molecular dynamics simulations up to 1000K. It exhibits anisotropic mechanical properties, with maximum Young’s modulus of 328.38N/m, and Poisson’s ratio ranging from 0.06 up to 0.50, respectively. Electronic structure analyses confirm its metallic behavior, while optical studies reveal anisotropic absorption in the visible and UV regions. For lithium-ion storage, AG shows strong Li adsorption (-2.3eV to -1.0eV), a high theoretical capacity of 836.78mAh/g, and a low average open-circuit voltage of 0.54V. Lithium diffusion barriers are as low as 0.30eV on the surface and 0.66eV between layers, with a diffusion coefficient of approximately 1 0 − 6 cm 2 /s. These features highlight AG as a promising anode material for high-performance lithium-ion batteries.